Características estruturais do dossel, produção de forragem e desempenho de cordeiros em pastos de tifton 85 sob lotação intermitente - Silva, Wilton Ladeira da [UNESP] (2014)
Use of intensive exploration in the sheep farming requires adoption of more refined techniques of management, like pastures, grazing and animals. In this context that the rotational stocking, among others, can be used to provide forage production in quantity and quality since the frequencies and intensities of defoliation are defined on criteria. The residual leaf area index (rLAI) of pastures has been used to indicate the time of interruption of grazing, in order to ensure the canopies, photosynthetically active components remaining after grazing. Thus, the objective this study was to compare the effects of rLAI in Tifton 85 pastures during rainy and dry seasons: 1) on the structural characteristics of pasture, 2) on the nutritive value of forage and on the performance of lambs, associated the supplementation strategies, 3) on the spatial distribution of morphological components of pastures and the ingestive behavior of lambs under grazing. Was used intermittent stocking with four days of occupation and frequency of desfoliation defined by light interception (LI 95%).Treatments were composed of four rLAI (0.8, 1.4, 2.0 and 2.6) in a randomized block design to evaluate the structural characteristics of pastures and ingestive behavior of animals. Associated with two supplementation strategies, treatments were composed by 4x2 factorial for observation of structural responses of pastures and animal performance. The pastures height at pre-grazing increased from 27.01 to 30.82 cm with increasing rLAI, and the total, stem and dead material dry masses were higher in swards grazed at higher rLAI. The herbage accumulation rate decreased from 84 to 56 kg ha-1 day-1 with increasing rLAI and decreased from 96 to 43 kg ha-1 day-1 from summer to winter. In pastures managed under smaller rLAI the highest grazing efficiencies were observed, however showed the highest regrowth intervals during the periods ...